HTLV-I/II and blood donors: determinants associated with seropositivity in a low risk population - Bernadette Catalan Soares; Anna Bárbara de F Carneiro Proietti; Fernando Augusto Proietti
OBJECTIVE: Blood donors in Brazil have been routinely screened for HTLV-I/II since 1993. A study was performed to estimate the prevalence of HTLV-I/II infection in a low risk population and to better understand determinants associated with seropositivity. METHODS: HTLV-I/II seropositive (n=135), indeterminate (n=167) and seronegative blood donors (n=116) were enrolled in an open prevalence prospective cohort study. A cross-sectional epidemiological study of positive, indeterminate and seronegative HTLV-I/II subjects was conducted to assess behavioral and environmental risk factors for seropositivity. HTLV-I/II serological status was confirmed using enzyme-linked immunosorbent assay (EIA) and Western blot (WB). RESULTS: The three groups were not homogeneous. HTLV-I/II seropositivity was associated to past blood transfusion and years of schooling, a marker of socioeconomic status, and use of non-intravenous illegal drugs. CONCLUSIONS: The study results reinforce the importance of continuous monitoring and improvement of blood donor selection process.